Modeling and observations of the north–south ionospheric asymmetry at low latitudes at long deep solar minimum - Balan, N.; Rajesh, P.K.; Sripathi, S.; Tulasiram, S.; Liu, J.Y.; Bailey, G.J. (My University, 2013)
Using the physics based model SUPIM and FORMOSAT-3/COSMIC electron density data measured at the long deep solar minimum (2008–2010) we investigate the longitude variations of the north–south asymmetry of the ionosphere at low latitudes (±30° magnetic). The data at around diurnal maximum (12:30–13:30 LT) for magnetically quiet (Ap ⩽ 15) equinoctial conditions (March–April and September–October) are presented for three longitude sectors (a) 60°E–120°E, (b) 60°W–120°W and (c) 15°W–75°W. The sectors (a) and (b) have large displacements of the geomagnetic equator from geographic equator but in opposite hemispheres with small magnetic declination angles; and sector (c) has large declination angle with small displacement of the equators; vertical E × B drift velocities also have differences in the three longitude sectors. SUPIM investigates the importance of the displacement of the equators, magnetic declination angle, and E × B drift on the north–south asymmetry. The data and model qualitatively agree; and indicate that depending on longitudes both the displacement of the equators and declination angle are important in producing the north–south asymmetry though the displacement of the equators seems most effective. This seems to be because it is the displacement of the equators more than the declination angle that produces large north–south difference in the effective magnetic meridional neutral wind velocity, which is the main cause of the ionospheric asymmetry. For the strong control of the neutral wind, east–west electric field has only a small effect on the longitude variation of the ionospheric asymmetry. Though the study is for the long deep solar minimum the conclusions seem valid for all levels of solar activity since the displacement of the equators and declination angle are independent of solar activity.
Keywords: Ionosphere; North–south asymmetry; Neutral wind; Electric field; Geomagnetic equators; Geographic equators